A comparison study of radio protocol AX.25 with Interchangeable data in VmeS (Vessel Messeging System) data communication and AIS (Automatic Identification System) - Ila Nur Mawati (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
Indonesia is maritime country, inhabitant of Indonesia is fisherman large enough. Fishship makes up constribution widely, in general, Communication in the sea on a ship uses a satellite communication system, but the system requires a relatively large cost. For solving it, Vessel Messaging System (VmeS) is used as basis radio communication to send between ship terminal in the sea with gateway Vmes in the land, in addition with wide enough territorial water, it needs reliable keeping of maritime region of country. One of system at this time can be used to support all activities is Automatic Identification System (AIS). AIS is a system that can be used to help in tracking ship position which has used in all ports automatically to obeserve ship condition and to prevent crashing between ships. In this study a data format is suitable for VMeS will be designed so that the interchangeable process can be carried out to AIS so it can be read by AIS receivers intended for vessels below 30 GT (Gross Tonnage) using the AX.25 protocol.Keywords: AIS, AX:25, interchangeable, VMeS.